ASSESSMENT OF THE EFFECTS OF EXTRACTS OF MEDICINAL PLANTS USED LOCALLY IN THE TREATMENT OF OSTEOARTHRITIS - Milanović, Isidora; Radivojević, Marija (ACADEMIC REVIEW, 2022)
Interest in herbal medicines and treatments has been growing in recent decades. The indications and safety of herbal preparations are based on the results of preclinical research. They are most often used as local preparations for the treatment of inflammatory and painful conditions of the musculoskeletal system, such as osteoarthritis. To evaluate the effectiveness of local application of a galenic preparation based on comfrey extract (10%) and rosemary essential oil (5%) in reducing symptoms caused by osteoarthritis. The sample consists of 7 female subjects aged 40 to 75 with a diagnosis of osteoarthritis. The results indicate an improvement in osteoarthritis symptoms after local application of galenic preparations based on comfrey extract (10%) and rosemary essential oil (5%). Local application of preparations based on rosemary and comfrey essential oil can be a rational therapeutic option for patients suffering from osteoarthritis and requires further and more detailed investigation of its effects.